‘I wasn't made to feel like a nut case after all’: A qualitative story completion study exploring healthcare recipient and carer perceptions of good professional caregiving relationships - Rebecca Feo; Jessica A. Young; Kristi Urry; Michael Lawless; Sarah C. Hunter; Alison Kitson; Tiffany Conroy (Health Expectations)
Abstract Background Professional caregiving relationships are central to quality healthcare but are not always developed to a consistently high standard in clinical practice. Existing literature on what constitutes high‐quality relationships and how they should be developed is plagued by dyadic conceptualisations; discipline, context and condition‐specific research; and the absence of healthcare recipient and informal carer voices. This study aimed to address these issues by exploring how healthcare recipients and carers conceptualise good professional caregiving relationships regardless of discipline, care setting and clinical condition. Design A qualitative story completion approach was used. Participants completed a story in response to a hypothetical stem that described a healthcare recipient (and, in some instances, carer) developing a good relationship with a new healthcare provider. Stories were analysed using reflexive thematic analysis. Participants Participants were 35 healthcare recipients and 37 carers (n = 72 total). Results Participants' stories were shaped by an overarching discourse that seeking help from new providers can elicit a range of unwanted emotions for both recipients and carers (e.g., anxiety, fear, dread). These unwanted emotions were experienced in relation to recipients' presenting health problems as well as their anticipated interactions with providers. Specifically, recipient and carer characters were fearful that providers would dismiss their concerns and judge them for deciding to seek help. Good relationships were seen to develop when healthcare providers worked to relieve or minimise these unwanted emotions, ensuring healthcare recipients and carers felt comfortable and at ease with the provider and the encounter. Participants positioned healthcare providers as primarily responsible for relieving recipients' and carers' unwanted emotions, which was achieved via four approaches: (1) easing into the encounter, (2) demonstrating interest in and understanding of recipients' presenting problems, (3) validating recipients' presenting problems and (4) enabling and respecting recipient choice. Participants' stories also routinely oriented to temporality, positioning relationships within recipients' and carers' wider care networks and biographical and temporal contexts. Conclusion The findings expand our understanding of professional caregiving relationships beyond dyadic, static conceptualisations. Specifically, the findings suggest that high‐quality relationships might be achieved via a set of core healthcare provider behaviours that can be employed across disciplinary, context and condition‐specific boundaries. In turn, this provides a basis to support interprofessional education and multidisciplinary healthcare delivery, enabling different healthcare disciplines, specialties, and teams to work from the same understanding of what is required to develop high‐quality relationships. Patient or Public Contribution The findings are based on stories from 72 healthcare recipient and carer participants, providing rich insight into their conceptualisations of high‐quality professional caregiving relationships.